Incidence Rates of Root Rot in Sweetpotato Caused by Cultivation Soil and Soil Microorganisms During Storage Periods - Kim, Sujung; Kim, Tae Hwa; Chung, Mi-Nam; Lee, YeongHoon; Lee, Im Been; Lee, HyeongUn; Park, Won (Frontiers in Plant Science, 2022)
Sweetpotatoes require a storage period for year-round use and improved sweetness by starch degradation. However, long-term storage can cause root rot, and a large amount of sweetpotatoes can be discarded. Root rot is typically caused by pathogenic soil-borne Fusarium spp., and the development of root rot induced by the characteristics of cultivating soil in stored sweetpotato has not yet been identified. In this study, the effect of Fusarium spp. and microbial community in the cultivated soil on the root rot of sweetpotatoes was to be elucidated. Wounded sweetpotato were treated in soil cultures inoculated with F. solani or F. oxysporum for two days, and showed symptoms of root rot after two months of storage. The three study fields (Naju, Yeongam A and B) were subjected to the same curing and storage treatments after harvest, and the incidence of root rot was 1.7- to 1.8-fold different after three months of storage. Across the three fields, concentrations of Fusarium spp. and of microbial communities differed according to the cultivation soil and period. In particular, Naju, which had the lowest incidence of root rot, had the lowest concentration of Fusarium spp. before harvest, and the smallest change in diversity of the microbial community during the cultivation period. However, tuberous roots harvested from the fields showed no significant differences in antioxidant activity or lesion size with the treatment of 106 conidia/mL F. solani. By solidifying the importance of cultivating soil and related microorganisms in the advancement of root rot of sweetpotato, our results may aid in preventing the decrease in the yield of cultivated sweetpotatoes through root rot control.